Прогнозування надійності елементів конструкцій з локальними корозійними пошкодженнями на основі статистичної оцінки статичної та циклічної міцності - Потопальська, Ксенія Євгенівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.02.09 – динаміка та міцність машин. – Національний технічний університет "Харківський політехнічний інститут", Харків, 2019. Дисертаційна робота присвячена розв’язанню актуальної науково-прикладної задачі, яка полягає у розвитку методів комп’ютерного аналізу залишкової міцності та прогнозування надійності елементів конструкцій енергетичного машинобудування, які за час тривалої експлуатації отримали корозійне зношення чи локальні пошкодження. Дослідження здійснені в рамках статистичних методів моделювання, а оцінка характеристик напружено-деформованого стану пошкоджених елементів конструкцій проводилась на основі методу скінчених елементів у тривимірній постановці. Розроблено підхід для теоретичної статистичної оцінки процесів накопичення втоми, який покладено в основу розрахункового методу прогнозу надійності елементів конструкцій, які мають набуті пошкодження корозійної природи на основі статистичної оцінки концентрації напружено-деформованого стану і процесів накопичення втоми. Здійснено комплексні дослідження можливих рівнів концентрації напружень у пошкоджених ділянках конструкцій з урахуванням експлуатаційної варіації навантаження та стохастичного характеру розвитку пошкодження корозійної природи. Виконано практичні розрахункові дослідження надійності елементів конструкцій, які використовуються у транспортуванні енергоносіїв та енергетичному машинобудуванні, що дало можливість розробити рекомендації щодо можливого подовження строку їхньої роботи та можливості відновлення працездатності.

Thesis for granting the Degree of Candidate of Technical sciences in specialty 05.02.09 – Dynamics and Strength of Machines. – National Technical University, "Kharkiv Polytechnical Institute", Kharkiv, 2019. The thesis is devoted to the solution of the actual scientific and applied task, which consists in the development of methods of computer analysis of residual durability and the prediction of reliability of elements of power engineering structures, which have been corrosive wear or local damage during long operation. The studies were performed within the framework of statistical modeling methods, and the evaluation of the characteristics of the deformed state of damaged structural elements was performed on the basis of the finite element method (FEM) in three-dimensional formulation. With the use of conceptual approaches for the theoretical assessment of fatigue accumulation processes within the framework of continual damage mechanics, improved methods for assessing the reliability and prediction of the residual life of damaged sections of structural elements, which, unlike known ones, are allowed to taken into account the statistical prediction of possible corrosion sizes. Complex researches of possible levels of stress concentration in the damaged sections of structures are made taking into account the operational variation of load and the stochastic nature of the development of corrosion damage. A statistical analysis and generalization of the obtained results were conducted. The investigation peculiarities of the stress concentration in the damaged areas of structural elements taking into account the operational load variations and the stochastic nature of the corrosion damage. The estimation of its effect on the residual strength is based on the Monte Carlo statistical simulation, taking into account the operational load and the statistical prediction of the possible variation in the size of the corrosion defects. An approach for theoretical statistical estimation of processes of fatigue accumulation is developed, which is the basis of the calculated method of predicting the reliability of structural elements, which will be determined by the simultaneous course of processes of fatigue accumulation and the development of corrosion defect. A set of practical calculation studies aimed at assessing the reliability of structural elements used in energy transportation and power engineering has been carried out and recommendations have been developed on the basis of the conducted research on the possible extension of their life and the possibility of restoration of efficiency. The parameters of damage and the number of cycles to failure of the elbow of the pipeline with a three-dimensional surface defect of mean size were determined taking into account the operational variation of load. The influence of composite bandage on the mean-sized pipeline resource is investigated. Calculations were made to determine the rational dimensions of the composite bandage for the curved portion of the mean-sized defect pipeline. The value of the internal pressure at which the equivalent stresses reach the strength limits in the pipeline with a bandage of different thickness is determined. The residual strength of the pump used in power engineering has been evaluated, taking into account the reduction of the wall thickness of the body parts from erosion-corrosion wear.
Predicting the reliability of structural elements with local corrosion damage based on the statistical evaluation of static and cyclic strength
Keywords: автореферат дисертації; надійність; ресурс; континуальна пошкоджуваність; втома; трубопроводи; відцентрові насоси; reliability; life-time; continuous damage; fatigue; pipelines; centrifugal pumps; 539.43:621.64